Renin-Angiotensin System and Coronavirus Disease 2019: A Narrative Review - Mascolo, Annamaria; Scavone, Cristina; Rafaniello, Concetta; Ferrajolo, Carmen; Racagni, Giorgio; Berrino, Liberato; Paolisso, Giuseppe; Rossi, Francesco; Capuano, Annalisa (Frontiers in Cardiovascular Medicine, 2020)
Although clinical manifestations of the 2019 novel coronavirus disease pandemic (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), are mainly respiratory symptoms, patients can also develop severe cardiovascular damage. Therefore, understanding the damage caused by SARS-COV-2 to the cardiovascular system and the underlying mechanisms is fundamental. The cardiovascular damage may be related to the imbalance of the renin-angiotensin-system (RAS) as this virus binds the Angiotensin-Converting-Enzyme 2 (ACE2), expressed on the lung alveolar epithelial cells, to enter into cells. Virus internalization may cause a downregulation of ACE2 on host cell surface that could lead to a local increased level of angiotensin II (AII) and a reduced level of angiotensin 1-7 (A1-7). An imbalance between these angiotensins may be responsible for the lung and heart damage. Pharmacological strategies that interfere with the viral attachment to ACE2 (umifenovir and hydroxychloroquine/chloroquine) or that modulate the RAS (analogous of A1-7 and ACE2, losartan) are in clinical development for COVID-19. The use of RAS inhibitors has also become a matter of public concern as these drugs may increase the mRNA expression and levels of ACE2 and impact the virulence and transmission of SARS-COV-2. Data on the effect of RAS inhibitors on ACE2 mRNA expression are scarce. Scientific societies expressed their opinion on continuing the therapy with RAS inhibitors in patients with COVID-19 and underlying cardiovascular diseases. In conclusion, RAS may play a role in SARS-COV-2-induced cardiac and pulmonary damage. Further studies are needed to better understand the role of RAS in COVID-19 and to guide decision on the use of RAS inhibitors.